Strategi Guru PAI dalam Mengembangkan Keterampilan, Kreatif dan Inovatif Siswa SMP Negeri 1 Langkat - Satria Wiguna; Nurdiana Syafitri; Khairunnisa Khairunnisa (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to analyze the learning strategies of Islamic Religious Education (PAI) applied by teachers in improving student creativity and competence at SMP Negeri 1 Langkat, North Sumatra. The research method used was qualitative, with data collection methods through observation, interviews, and documentation. Observation was conducted to identify the interaction and application of learning strategies by PAI teachers, while in-depth interviews with teachers and students provided information related to the effectiveness of the method. The results showed that 1) Teachers' creativity in combining learning methods, such as discussions, projects, and the use of technological media, was able to create an interesting and interactive learning atmosphere, which had a positive impact on students' understanding of the teaching materials. 2) Improved facilities and infrastructure as well as curriculum adjustments also support the effectiveness of learning, so that students are more motivated to actively participate in the learning process. PAI teachers not only convey religious concepts, but also equip students with balanced cognitive, affective, and psychomotor abilities, in accordance with Bloom's taxonomy theory. This study concludes that innovation in learning methods and adequate facility support are key in improving students' learning skills and interest.